Effect of heat treatment on mechanical properties of type-304 austenitic stainless steel - Pham, Hang Thi; Nguyen, Thong Chung (Vietnam Journal of Mechanics, 2025)
In this study, the effects of cryogenic treatment and heat treatment on the microstructural evolution and mechanical properties of type-304 austenitic stainless steel are investigated. Cryogenic treatment is conducted in a liquid nitrogen environment at -196°C, both with and without a quenching process. The experimental results indicate that traditional heat treatment processes do not lead to improvements in hardness or phase transformation. Although a modest increase in the ultimate tensile strength is observed with prolonged immersion in liquid nitrogen, deep cryogenic treatment does not produce a significant enhancement in the tensile properties of the examined material. Among the cases examined, water-quenched heat treatment without cryogenic treatment demonstrates a considerable increase in ductility. Additionally, significant differences in microstructure and hardness are observed at different locations of the tensile specimen due to martensitic transformation from the austenitic phase during plastic deformation. Consequently, improvement in the mechanical properties of the steel is not a result of the heat treatment process; rather, the heat treatment affects the stability of the austenitic phase, thereby influencing the potential for martensitic transformation during plastic deformation.